1992
DOI: 10.2169/internalmedicine.31.549
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Idiopathic Plasmacytic Lymphadenopathy with Polyclonal Hypergammaglobulinemia.

Abstract: A 51-year-old male was admitted because of eyelid edema and anosmia, which developed in 1985. He showed bilateral cervical lymphadenopathy, with nodes larger than 2 x 2cm, and remarkable eyelid edema. Anemia, hyperimmunoglobulinemia with hypo-albuminemia (no M-protein) and liver dysfunction were found. Bone marrow, renal function, urine analysis and LDH level were normal. Cervical lymph node biopsy showed interfollicular proliferation of plasma cells without any malignant appearance. On day 3 of oral prednisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although there has been some controversy concerning the treatment of MCD, therapies such as chemotherapy including steroids were effective in improving renal insufficiency [20]. In this case, the combination therapy of methylprednisone and cyclophosphamide improved not only PRCA but also renal insufficiency.…”
Section: Discussionmentioning
confidence: 76%
“…Although there has been some controversy concerning the treatment of MCD, therapies such as chemotherapy including steroids were effective in improving renal insufficiency [20]. In this case, the combination therapy of methylprednisone and cyclophosphamide improved not only PRCA but also renal insufficiency.…”
Section: Discussionmentioning
confidence: 76%
“…Mori et al developed the following diagnostic criteria for IPL: (i) polyclonal hyperimmunoglobulinemia without M protein (Ig G exceeding 4500 mg/dL); (ii) systemic lymphadenopathy (>1.8 cm in diameter) with high plasmacytic infiltration but without deterioration of the basic structure; (iii) the exclusion of other diseases including infection, collagen, and autoimmune diseases, hepatitis and liver cirrhosis . The case described here fulfilled these criteria, and the diagnosis of IPL was formulated.…”
Section: Discussionmentioning
confidence: 95%
“…The clinical features are polymorphic because of the involvement of several organs (the skin, and pulmonary, digestive, and renal systems) . The treatment of IPL has not yet been established, but some authors have indicated the efficacy of corticosteroid treatment, anticancer chemotherapy, and monoclonal antibodies .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 IPL was first described by Mori et al in 1980 as systemic lymphadenopathy and hypergammaglobulinemia with increased inflammatory markers and serum interleukin-6 (IL-6) with indolent clinical courses. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In 2008, Kojima et al reported 28 iMCD cases (18 IPL and 10 non-IPL). 22 Of note, 40% of the non-IPL patients were diagnosed with autoimmune diseases, such as Sjögren's syndrome (SjS) and immune thrombocytopenic purpura, and they exhibited thrombocytopenia, anasarca, fever, reticulin fibrosis or renal insufficiency, and organomegaly (TAFRO) symptoms.…”
mentioning
confidence: 99%